Multiculturalism and Indigenous Law: current state of this diversity management model with respect to indigenous peoples’ law in Mexico - Angeles-Hernandez, Elias (2025)
This paper seeks to answer the question of the current state of multiculturalism in relation to Indigenous Law as a legal system in Mexico. In this context, the model of diversity management—multiculturalism—has been reflected, among other policies, in amendments to the Mexican Constitution concerning indigenous peoples and their legal systems. Despite representing progress in the recognition and treatment of cultural complexity, these amendments have not yet served as an effective channel to position, articulate, or visualize Indigenous Law as a genuine legal system. This is because the State continues to determine its scope, meaning, interpretation, and application. Therefore, given the limited outcomes in this area, it is possible to speak of a crisis of multiculturalism in this regard, since instead of addressing the reality, validity, and enforceability of Indigenous Law, it has been reduced to mere recognition. This situation compels us to consider other approaches or emerging paradigms that can respond to a context in which ethnic and cultural differences are the norm—such as interculturality.